Perencanaan Kawasan Wisata Ngebel, Kabupaten Ponorogo untuk Meningkatkan Kesejahteraan Masyarakat - Ekawati Lidya Agustina; Nurul Azizah Freya Fidela; Alifah Nurul Zakiyah; Naila Darojatil Ulya; Yusuf Adam Hilman (Pusat Riset dan Inovasi Nasional, 2024)
The Ngebel area is an area that can be developed as an integrated tourist destination, based on its potential, starting from: natural, cultural, social - community potential, so that integrative efforts related to regional development can be carried out to strengthen the Ngebel area as a tourism epicentrum in Ponorogo Regency, this study aims to determine the extent to which the development of the Ngebel area can be carried out, by involving the potential and also the threats of the area. The research method used is descriptive qualitative, with data collection techniques in the form of observation and also interviews and documentation. From the results of the study it was found that the Ngebel area has the potential for art, nature and also the strength of the community that can be used as capital in regional development.